2018
DOI: 10.1186/s13033-018-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct medical costs for patients with schizophrenia: a 4-year cohort study from health insurance claims data in Guangzhou city, Southern China

Abstract: BackgroundSchizophrenia is one of the leading public health issues in psychiatry and imposes a heavy financial burden on the healthcare systems. This study aims to report the direct medical costs and the associated factors for patients with schizophrenia in Guangzhou city, Southern China.MethodsThis was a retrospective 4-year cohort study. Data were obtained from urban health insurance claims databases of Guangzhou city, which contains patients’ sociodemographic characteristics, direct medical costs of inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
(69 reference statements)
4
14
0
1
Order By: Relevance
“…Individual patients who had a stroke were divided into different groups according to factors that impacted their utilisation of inpatient health services. 17 Using ICD-10, ischaemic stroke types were defined by I63, I63.0–5 (cerebral infarction due to thrombosis of precerebral arteries, embolism of precerebral arteries, unspecified occlusion or stenosis of precerebral arteries), I63.8 and I63.9 (other and unspecified cerebral infarction). Based on bed size, location and functional orientation, hospitals in China were divided into primary hospitals, with less than 100 beds, providing basic health services to residents in a community; secondary hospitals, with 100–500 beds, providing comprehensive health services to several communities as well as medical training and regional-based research and tertiary hospitals, with over 500 beds, providing complex healthcare for several districts and undertaking advanced medical education and research.…”
Section: Methodsmentioning
confidence: 99%
“…Individual patients who had a stroke were divided into different groups according to factors that impacted their utilisation of inpatient health services. 17 Using ICD-10, ischaemic stroke types were defined by I63, I63.0–5 (cerebral infarction due to thrombosis of precerebral arteries, embolism of precerebral arteries, unspecified occlusion or stenosis of precerebral arteries), I63.8 and I63.9 (other and unspecified cerebral infarction). Based on bed size, location and functional orientation, hospitals in China were divided into primary hospitals, with less than 100 beds, providing basic health services to residents in a community; secondary hospitals, with 100–500 beds, providing comprehensive health services to several communities as well as medical training and regional-based research and tertiary hospitals, with over 500 beds, providing complex healthcare for several districts and undertaking advanced medical education and research.…”
Section: Methodsmentioning
confidence: 99%
“…One explanation is that UEBMI offers a comprehensive coverage while URBMI focused on inpatient support and catastrophic illness for outpatient services. Some basic outpatient services were not covered by URBMI (33), consequently URBMI patients visited hospital less frequently than UEBMI members (30). Our results also showed that UEBMI members had a larger number of outpatient visits than URBMI members and most of the outpatients in our sample were covered by UEBMI (71.1%).…”
Section: Discussionmentioning
confidence: 54%
“…Since socioeconomic status and education level have been found to be important in uential factors in pre-hospital delay, which will affect the ALOS for ischemic stroke inpatients (28), we speculate that patients covered by UEBMI had higher levels of education and socioeconomic status than URBMI members, as well as paying more attention to their personal health (15). Consequently, UEBMI members sought medical treatment at higher level of hospitals and were more willing to consume additional health services, which were not covered by the health insurance, than URBMI patients (29,30). Second, different therapeutic schedules could be adopted by doctors according to patients' insurance status, and the UEBMI insurance scheme bene t schedule was more generous, as shown in Table 1, and offered a higher reimbursement rate than URBMI (14,31).…”
Section: Discussionmentioning
confidence: 99%
“…Individual stroke inpatients were divided into different groups according to factors that impacted their utilization of inpatient health services (31). Using ICD-10, ischemic stroke types were defined by I63 and i63.0-5 (cerebral infarction due to thrombosis of precerebral arteries, embolism of precerebral…”
Section: Discussionmentioning
confidence: 99%